Bacterial Interstitial Nephritis in Children - Bobadilla Chang, Fernando (1999)
OBJECTIVE: To assess the diagnosis approach to urinary tract infections in children. MATERIAL AND METHODS: Medical records from 103 children with diagnosis of interstitial bacterial nephritis were retrospectively reviewed. Diagnosis was supported by the dramatic involvement of renal parenquima, which is not addressed as "urinary tract infection". RESULTS: From all 103 patients, 49 were 2-years-old or younger, 33 were between 2 and 5-years-old, and 21 were between 6 to 10. Clinical picture included physical findings such as those related to renal involvement (pallor, dry skin, dry tongue, decreased urinary density) and inflammatory responses to the microorganism (hepatomegaly, anemia, leukocyturia and hematuria). CONCLUSIONS: Children with interstitial bacterial nephritis showed physiologic and clinical signs which have not been observed in adults, features accounted by physicians in order to achieve an accurate diagnosis.